2011
DOI: 10.1089/pho.2009.2749
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Combination of Infrared and Red Laser Light on the Healing of Cutaneous Wounds Infected by Staphylococcus aureus

Abstract: The results of the present study indicate that laser phototherapy has a positive effect on the healing of infected wounds, particularly with the association of λ680 + λ790 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
1
14
0
3
Order By: Relevance
“…The present study used a combination of infrared (λ808 nm) and red laser (λ660 nm), because some studies have suggested that this association is more effective in reducing the inflammatory process and accelerating tissue repair, as different wavelengths would have different absorption and penetration ( 12 , 27 - 29 ). Irradiation of the root surface with infrared laser was based on findings of Carvalho et al ( 9 ) and irradiation of the alveolar walls and vestibular/palatine mucosa with red laser was based on findings of Vilela et al ( 10 ), who showed less root resorption areas in laser groups using their respective wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…The present study used a combination of infrared (λ808 nm) and red laser (λ660 nm), because some studies have suggested that this association is more effective in reducing the inflammatory process and accelerating tissue repair, as different wavelengths would have different absorption and penetration ( 12 , 27 - 29 ). Irradiation of the root surface with infrared laser was based on findings of Carvalho et al ( 9 ) and irradiation of the alveolar walls and vestibular/palatine mucosa with red laser was based on findings of Vilela et al ( 10 ), who showed less root resorption areas in laser groups using their respective wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Low-intensity laser therapy is one of the clinical therapeutic modalities that has been used for wound healing. Previous studies of laser treatments have demonstrated that low-intensity laser therapy accelerates and facilitates wound healing 17 , 18 , 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, for the pulsed 890 nm laser, Ezzati et al [28] observed the destructive effect only when doses of 11.7 J/cm 2 were given, but not to 2.3 J/cm 2 . Santos et al [29] observed a positive effect on wound healing in infected Wistar rats on the most advanced inflammatory stages by using laser 680 and 790 nm, with dose of 5 J/cm 2 . Also, Vasheghani et al [30], despite verifying an improvement in the rat ulcers, observed no effect of the laser 890 nm, 0.396 J/cm 2 on S. aureus .…”
Section: Discussionmentioning
confidence: 99%